Framework for Management of Post-Conflict Waste in Libya - Ali, Ashraf; Ezeah, Chukwunonye (European Scientific Journal, ESJ, 2017)
An important aspect of the Libyan conflict since the 2011 Arab Spring is the generation and management of huge volumes of construction and demolition (C&D) type waste, arising from conflict-related damage to the built environment. Estimates put the amount of Post-Conflict Waste (PCW) at about 82 million tonnes, much of which comprises potentially useful materials that could be reused or further processed and used in construction and other sectors of the economy. This paper presents and discusses the challenges that affect the use, reuse and recycling of such materials. To validate findings from literature, a pilot questionnaire survey of 70 professionals working in the waste management sector was carried out to identify the barriers constraining sustainable management of solid waste stream in three major Libyan cities. Data analysis was carried out using SPSS version 20.0. Based on the identified barriers, a framework for sustainable management of post-conflict waste arising in Libya has been designed in line with the medium-term infrastructure development objectives of the Libyan government. The paper recommends an urgent revision of applicable legislation and the formulation of new ones to address identified gaps in sustainable waste management. It is envisaged that results from this study will help underpin post-conflict sustainable development goals in Libya.